A Clinical Trial Comparing Smoking Cessation Interventions at Two Levels of Intensity in Stroke Patients, Stratified by the Presence of Insular Cortex Lesions. Issue 1 (10th July 2021) - Suñer-Soler, Rosa; Grau-Martín, Armand; Terceño, Mikel; Silva, Yolanda; Maldonado, Eduardo; Gras, Maria Eugenia; Font-Mayolas, Sílvia; Rodrigo-Gil, Joana; Serena, Joaquín
Abstract: Introduction: Smoking is a stroke risk factor but the most efficient way to promote cessation is unknown. The smoking behavior in patients during the first 2 years post-stroke is studied comparing brief advice and intensive behavioral counseling interventions, taking into consideration biological, psychological, and social factors. Methods: Randomized clinical trial of 196 stroke patients, stratified by the presence or not of an insular cortex lesion, with two levels of smoking cessation intervention. Results: The study retention rate was 85.2%. Abstinence point prevalence at three months after stroke was 50% in the brief advice group and 51.7% in the intensive behavioral counseling group ( p = .82) and at 24 months, 48.3% in the brief group and 47.5% in the intensive group ( p = .92). Most relapses occurred in the first weeks. After 3 months the curves separated with fewer events in the intensive group and at 24 months the Hazard Ratio was 0.91 (95% CI = 0.61 to 1.37; p = .67). Twenty-four months after stroke, patients with an insular lesion were more likely to be abstinent (OR 3.60, 95% CI = 1.27 to 10.14), as were those who lived with a partner (OR 2.31, 95% CI = 1.17 to 4.55) and those who were less dependent (OR 0.84, 95% CI = 0.73 to 0.97). Conclusions: A high percentage of patients gave up smoking in both intervention groups with no significant differences between the two. The effect of the insular lesion on smoking cessation, which is early and continued after two years, is particularly notable. Implications: This two-year clinical trial compares for the first time the efficacy of two different intensities of smoking cessation intervention in stroke patients, taking into consideration the effect of the insula. Good results are obtained both in the short and medium-term in people with stroke, especially when this is accompanied by an insular cortex lesion, but there is no evidence that better results are obtained with longer, more time-intensive, and possibly more costly follow-ups obtain better results than are obtained with briefer interventions.